THE IMPLICATIONS OF ENERGY TRANSITION ON SUSTAINABLE SUPPLY CHAIN MANAGEMENT PRACTICES IN THE OIL AND GAS INDUSTRY - Wan Ahmad, Wan Nurul Karimah; P. De Brito, Marisa; A. Tavasszy, Lorant (Journal of Technology Management and Business, 2015)
The oil and gas (O&G) industry is increasingly pressured to manage its supply chain sustainably due to the negative impact of its activities and products on the environment and society. Unsustainable exploitation of the O&G has also led to concerns about its future availability, thus the security of energy supply. These issues resulted in the call for the transition to an energy system that favours low carbon and renewable sources. The O&G are expected to respond to these pressures by developing strategies that could enhance its competitiveness and compatibility with the future energy systems. As yet, little is known about the strategies especially with regard to sustainable supply chain management (SSCM) aspects. Therefore, this study aims to add to the discussion by focusing on understanding the implications of energy transition to SSCM practices in the O&G industry. It employs content analysis of sustainability reports of 30 O&G companies. The findings indicate that although 18 companies are involved in the research and development of alternative energy, the main focus is on developing unconventional O&G to increase fuel supply bases. In addition, among the alternatives, biofuels is the most preferred energy option due to its compatibility with the companiesâ€™ existing business and infrastructure. Overall, there are considerable limitations in the discussions of the SSCM strategy in the reports. We find that the sustainability of the unconventionalsâ€™ production processes received more attention than supplier and logistics management. The strategies for sustainable supply chain of the alternatives, except for biofuels, are hardly discussed or absent from the report. The findings could be useful to industry practitioners in decision making processes to improve existing SSCM practices during the transition, and to academics to identify areas for further investigations.Â